ACCEPTABILITY AND NUTRITIONAL CONTENT TEST OF CASSAVA SKIN FLOUR CHIPS IN PANTAI LABU BARU VILLAGE, PANTAI LABU SUB-DISTRICT - Rista Wahyuni; Rani Suraya (Journal of Gender and Social Inclusion in Muslim Societies, 2025)
Cassava peel flour offers potential as a sustainable and nutritious ingredient for food diversification. This study evaluated the sensory acceptability and nutritional value of cassava peel flour chips produced in Pantai Labu Baru Village, North Sumatra. A randomized complete design (CRD) with four formulations (F0 = 0%, F1 = 20%, F2 = 30%, F3 = 40% cassava peel flour) and three replicates was applied. Twenty untrained panelists aged 18-25 years participated in sensory testing under ethical consent and the sensory evaluation code of ethics, using 3-digit blinding codes and randomized sample order. Each chip sample (≈30 °C) was evaluated for color, aroma, taste, and texture, with water provided for rinsing between samples. Data were analyzed using RM-ANOVA (Friedman test as non-parametric confirmation), followed by post-hoc Duncan and effect-size reporting (η²). Nutritional composition (AOAC/ISO methods) included proximate, energy, Ca, P, crude fiber, and oil content; HCN levels were tested in raw flour and final products after detoxification (soaking 3 days, 5% salt, 1:4 w/v water ratio). Results showed significant sensory differences (p < 0.05); F1 and F2 achieved the highest acceptability, with balanced color, aroma, and texture. Calcium and phosphorus contents increased with substitution up to 30%, reaching 0.13% Ca and 0.10% P in F2. Higher levels (F3) reduced sensory appeal and calcium retention, likely due to heat degradation and fiber-mineral interaction. HCN content was reduced to < 1 mg/kg after detoxification. Incomplete data on lipid oxidation and microbiological stability were noted as study limitations and will be addressed in further research. These findings indicate that moderate substitution (20-30%) optimizes sensory quality and mineral enhancement, supporting cassava peel utilization as a nutritious, eco-friendly food material.